2016
DOI: 10.1186/s12939-016-0364-2
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic gradients in early childhood health: evidence from Bangladesh and Nepal

Abstract: BackgroundA large literature has developed researching the origins of socioeconomic gradients in child health in developed countries. Particularly, this research examines the age at which these gradient effects emerge and how they change across different stages of childhood. However, similar research on developing countries is limited.MethodsThis paper examines the socioeconomic gradients in early childhood health in two developing countries, Bangladesh and Nepal using the 2011 Demographic and Health Surveys. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Surprisingly, despite the importance of the socioeconomic environment, the moderating effect of income or household socioeconomic status (SES) for the age pattern of stunting or, alternatively, height-for-age z-scores (HAZ) has not been systematically described. Existing studies are largely limited to rough split-sample analyses and only a small set of countries 12–21. While Alderman and Headey22 make use of a much larger data set, consisting of Demographic and Health Surveys (DHS) implemented in 57 countries, to describe various determinants of HAZ in children below the age of 5 years, they limit their focus to seven age groups and only base their analysis on SES terciles rather than quartiles.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, despite the importance of the socioeconomic environment, the moderating effect of income or household socioeconomic status (SES) for the age pattern of stunting or, alternatively, height-for-age z-scores (HAZ) has not been systematically described. Existing studies are largely limited to rough split-sample analyses and only a small set of countries 12–21. While Alderman and Headey22 make use of a much larger data set, consisting of Demographic and Health Surveys (DHS) implemented in 57 countries, to describe various determinants of HAZ in children below the age of 5 years, they limit their focus to seven age groups and only base their analysis on SES terciles rather than quartiles.…”
Section: Introductionmentioning
confidence: 99%
“…Even though Bangladesh has one of the highest prevalence of underweight in the world, few studies have identified the socioeconomic factors responsible for child underweight [ 24 30 ]. Most of the studies conducted in Bangladesh suggested that maternal education is a strong and significant predictor for child underweight [ 24 , 28 , 29 , 31 , 32 ]. A recent study by Devkota et al [ 28 ] established a positive association of WAZ (weight-for-age z score) with the level of maternal education.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies conducted in Bangladesh suggested that maternal education is a strong and significant predictor for child underweight [ 24 , 28 , 29 , 31 , 32 ]. A recent study by Devkota et al [ 28 ] established a positive association of WAZ (weight-for-age z score) with the level of maternal education. Mohsena et al [ 24 ] explored the Bangladesh Demographic and Health Survey (2004) Data and found that higher levels of maternal education are associated with lower risk of underweight.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations